Evaluation of five essential oils for the control of food - spoilage and mycotoxin producing fungi - Gömöri, Csilla (Acta Biologica Szegediensis, 2013)
The inhibition of growth and aflatoxin production by essential oils (EOs) of cinnamon, clary sage, juniper, lemon and marjoram were investigated on food-spoilage fungi Aspergillus parasiticus var.globosus, Fusarium graminearum and Fusarium culmorum. The antifungal effect of the EOs was observed by determination of growth-rate (mm/day) and antifungal index (%) using reversed Petri-dish method. Aflatoxin production of A. parasiticus was monitored by thin layer chromatography (TLC). The growth of A. parasiticus was significantly decreased (P<0,001) by marjoram and clary sage EOs. TLC results revealed only a slight effect on aflatoxin production: cinnamon and clary sage EOs found to decrease the amount of aflatoxin B1 and G2. F. graminearum and F. culmorum showed almost similar response to the EOs. In both cases cinnamon EO caused a total inhibition of growth, while lemon EO was ineffective. Juniper significantly (P<0,003) inhibited the growth of F. culmorum but had no effect on F. graminearum. The EOs tested in this study may be potential antimicrobial compounds for use as food preservatives and anti-aflatoxin agents.